2003
DOI: 10.4141/a03-065
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and in situ degradability of whole crop faba bean, pea, and soybean silages

Abstract: P. 2003. Characteristics and in situ degradability of whole crop faba bean, pea, and soybean silages. Can. J. Anim. Sci. 83: 793-799. The objective of this study was to determine the ensiling characteristics and ruminal nutrient degradabilities of faba bean (FS, Vicia faba L.), soybean (SS, Glycine max (L.) Merr.) and pea (PS, Pisum sativum L.) silages. Forages were harvested between the beginning-and full-seed stages and ensiled in mini-silos for 0, 2, 4, 16, and 45 d. Two lactating Holstein cows fitted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
7
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
7
25
7
2
Order By: Relevance
“…This is agreement with Coffey et al (1995), who reported differences in DM content between Bay soybean forage and Stafford soybean forage at pre-ensiling. Mustafa & Seguin (2003) reported 264 g DM/kg in wilted forage soybean before ensiling, comparable with Link forage soybean before ensiling in the current study. However, the DM in forage soybean cultivars before ensiling was higher than 248 g DM/kg reported by Tobia et al (2008) in unwilted forage soybean at ensiling.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This is agreement with Coffey et al (1995), who reported differences in DM content between Bay soybean forage and Stafford soybean forage at pre-ensiling. Mustafa & Seguin (2003) reported 264 g DM/kg in wilted forage soybean before ensiling, comparable with Link forage soybean before ensiling in the current study. However, the DM in forage soybean cultivars before ensiling was higher than 248 g DM/kg reported by Tobia et al (2008) in unwilted forage soybean at ensiling.…”
Section: Discussionsupporting
confidence: 63%
“…However, the present study agrees with that of Zhang et al (2013), who reported reduced CP content with LD inoculation in Urtica cannabina silage. Other studies (Mustafa & Seguin, 2003;Lima et al, 2013;Touno et al, 2014) have recorded CP values in soybean silage that are higher than in the soybean silage of the present study, which might be attributed to the different soybean forage cultivars used amongst these studies. Inoculation did not affect EE contents in soybean silages of the present study (Table 3).…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations